South Korea's Gastrodiplomacy Towards Indonesia Through K-Dramas - Anastasia Wiwik Swastiwi; Evy Angela Siringo Ringo (Faculty of Social and Political Science Universitas Maritim Raja Ali Haji, Indonesia, 2023)
Relations between Indonesia and South Korea have started since 1973. One form of diplomacy in relations between South Korea and Indonesia is gastrodiplomacy. Gastrodiplomacy is public diplomacy that uses food or culinary culture with the aim of conveying certain messages. In public diplomacy, gastrodiplomacy aims to practice communication between state to public in promoting state cuisine to the international public through understanding, informing and influencing foreign audiences. These three stages are indispensable for South Korea in promoting gastrodiplomacy in Indonesia. In this study, public diplomacy was conducted to analyze the efforts made by state and non-state actors in introducing South Korean cuisine to Indonesia. The research method used is descriptive qualitative, with data collection techniques using literature study. The results of this study found that South Korean gastrodiplomacy uses the K_drama instrument. Korean dramas have been considered successful because they are able to provide a strong influence for the international public to continue watching and provide a sense of curiosity about how Korean culture and food are always displayed. Gastrodiplomacy that has been carried out by South Korea in Indonesia has given good results for its culinary products to continue to develop and be marketed in the Indonesian market.